Characterising ISWI chromatin remodeler in Trypanosoma cruzi - Yirys Díaz-Olmos; Michel Batista; Adriana Ludwig; Fabricio K Marchini (Memorias do Instituto Oswaldo Cruz)
BACKGROUND Imitation SWItch (ISWI) ATPase is the catalytic subunit in diverse chromatin remodeling complexes. These complexes modify histone-DNA interactions and therefore play a pivotal role in different DNA-dependent processes. In Trypanosoma cruzi, a protozoan that controls gene expression principally post-transcriptionally, the transcriptional regulation mechanisms mediated by chromatin remodeling are poorly understood. OBJECTIVE To characterise the ISWI remodeler in T. cruzi (TcISWI). METHODS A new version of pTcGW vectors was constructed to express green fluorescent protein (GFP)-tagged TcISWI. CRISPR-Cas9 system was used to obtain parasites with inactivated TcISWI gene and we determined TcISWI partners by cryomilling-affinity purification-mass spectrometry (MS) assay as an approximation to start to unravel the function of this protein. FINDINGS Our approach identified known ISWI partners [nucleoplasmin-like protein (NLP), regulator of chromosome condensation 1-like protein (RCCP) and phenylalanine/tyrosine-rich protein (FYRP)], previously characterised in T. brucei, and new components in TcISWI complex [DRBD2, DHH1 and proteins containing a domain characteristic of structural maintenance of chromosomes (SMC) proteins]. Data are available via ProteomeXchange with identifier PXD017869. MAIN CONCLUSIONS In addition to its participation in transcriptional silencing, as it was reported in T. brucei, the data generated here provide a framework that suggests a role for TcISWI chromatin remodeler in different nuclear processes in T. cruzi, including mRNA nuclear export control and chromatin compaction. Further work is necessary to clarify the TcISWI functional diversity that arises from this protein interaction study.